Financial Performance and Operating Cash Flow as Determinants of Financial Distress - Muhammad Rifki Abdul Ghoni; Rediyanto Putra (Golden Ratio of Auditing Research, 2026)
Financial distress is a critical issue that may threaten corporate sustainability, particularly in the property and real estate sector, which is characterized by high capital intensity, long project cycles, and substantial dependence on external financing. Understanding the factors influencing financial distress is essential for stakeholders in evaluating corporate financial conditions and making informed decisions. This study investigates the effects of liquidity, profitability, leverage, and operating cash flow on financial distress among property and real estate companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The study adopts a quantitative approach using secondary data obtained from companies’ annual financial statements. A total of 40 companies were selected through purposive sampling, resulting in 200 firm-year observations. Financial distress was measured using the Modified Altman Z-Score model. Data were analyzed using descriptive statistics, classical assumption tests, and multiple linear regression analysis with IBM SPSS Statistics 27. The results indicate that liquidity and profitability have a positive and significant effect on financial distress, while leverage has a negative and significant effect on financial distress. Meanwhile, operating cash flow does not have a significant effect on financial distress. These findings suggest that variations in liquidity, profitability, and leverage play an important role in explaining financial distress conditions in property and real estate companies, whereas operating cash flow is not a determining factor. This study contributes to the financial distress literature by providing empirical evidence from the Indonesian property and real estate sector during the post-pandemic recovery period. The findings also offer practical implications for investors and corporate managers in assessing financial performance, identifying potential financial distress risks, and formulating strategies to enhance long-term financial sustainability.